Educational needs and opportunities for adaptation of students with disabilities and persons with health limitations in the tertiary education system - M. V. Iontseva; S. A. Grishaeva; M. A. Ayvazyan (Вестник университета)
The article is devoted to the definition consideration of the educational needs of persons with health limitations (hereinafter – HL) and disabled persons in the tertiary education system; the aspects in which these needs are expressed. The article highlights the adaptation possibilities of disabled people in the tertiary education system, as well as the specifics of the organization and goals of an educational institution for teaching people with HL. The authors identify the barriers of social relations faced by students with HL, disabled students and their teachers at universities; analyze the degree of involvement of a student with HL in the educational process. The paper pays attention to the main approaches to the organization of educational activities of persons with HL and disabled people, namely: competence-based, project-based and activity-based approaches. The main types of inclusion, identified on the basis of medical indicators, as conditions for organizing the training of students with HL and disabled students are considered. It is determined that the education organization at the university of students with HL allows to adapt educational programs to the special needs of students, depending on the state of health of students with HL and of disabled students.